USE OF TECHNOLOGY 3 DIMENSIONS AS GEOMETRY LEARNING METHOD IN CHILDREN AGED 5-6 YEARS - Khusnul Khotimah (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Geometry is an important field for life and need to be teaching as early as possible so that children’s understanding ability about space and shape can get better. Old learning geometry methode only using paper and pencil while now as techonologies growing up so fast, teacher and school start using technology as a media learning for geometry. By using technology, such as; virtual reality, dynamics geometry software, etc, children can more develop and explore their geometric ability and get to know more about geometry. Plus, children around age 5- years old usually learning something through concrete so that’s why we need techonology as a media to make geometric learning more realistic so that children can develop their cognitive ability, especially in geometry field. This is qualitative study and using literature study as a collecting data methode. So, the conclusion is that by using technology as a geometry learning media is really help for children aged 5-6 years old to get to more understand about geometry.